Delve into the Triple P Funnel framework: a key to crafting teacher professional development among pre-service teacher in Zhaoqing, Guangdong. - Mohd Ayub, Ahmad Fauzi; Mohamed Mokhtar, Marzni; Mohd Ayub, Ahmad Fauzi (Faculty of Educational Studies, Universiti Putra Malaysia, 2024)
The field of education is currently undergoing a revolution centered on artificial intelligence. With the help of advanced intelligent tools, smart education is optimizing the allocation of resources and contributing to educational equity. It also aims to realize the personalization, interactivity, and intelligence of the teaching process, making learning simpler, more interesting, more effective, and more sustainable. This quasiexperimental study aimed to investigate the implementation of The Trip Funnel Framework on teacher professional development among pre-service teachers in Zhaoqing, Guangdong. A total of 120 pre-service teachers who enrolled in the Modern Educational Technology Application courses were assigned to the intervention (n=60) and control groups (n=60) for one semester (15 weeks).